Visual Rhetorical Devices Between Rhetoric and Literature - Al-Breiki, Fatima Abdul Rahman (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aims to reconsider rhetorical studies, which are perceived to be divided into two aspects: a phonetic aspect concerned with the rhythm of the words themselves, and a visual aspect related to the mental images formed when viewing a specific artistic image or using tools primarily based on vision. The study seeks to identify and categorize these rhetorical tools and place them in their appropriate contexts. Methodology: The research adopts an inductive analytical approach, tracking rhetorical tools used from both phonetic and visual perspectives and analyzing them to draw conclusions about the possibility of simplifying rhetorical studies that have become complex due to contemporary rhetoricians and removing aspects belonging to the modern "visual literary arts." Results: The research revealed the existence of rhetorical tools that vary between phonetic and visual aspects, with differences arising from the cultures in which they originated. Many rhetorical studies found in the works of contemporary rhetoricians contain visual tools that have been analyzed in this research. Conclusion: The research suggests the existence of new rhetorical tools suitable for modern digital culture, and it recommends that researchers interested in this topic explore these tools.